Pengaruh Pelatihan Sensitivitas Interkultural guna Menurunkan Intergroup Bias pada Karyawan - , YANIES NOVIRA; , Prof. Dr. Djamaludin Ancok, Psi. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Population movements, rapid technological development and globalization of the economy led to the increasing contact between cultures and cultural diversity, especially in an organizational environment. Issues of cultural diversity in the form of intergroup bias, such stereotype, prejudice and discrimination can hinder the continuity of interaction of workers within the organization. Related to the interaction and cooperation between cultures is important as to improve intercultural sensitivity. This experimental study aims to improve intercultural sensitivity in order to reduce intergroup bias through intercultural sensitivity training. Subjects were civil servants or civil servants who are 32 who were divided into 2 groups, ie 16 experimental group and 16 control group. Intercultural Sensitivity training as treatments. Measurements were performed before and after training. Measuring instruments used are scale intergroup bias, manipulation check using intercultural sensitivity scale. Analysis of research data using t-test. The results indicate there are differences in the level of intergroup bias in the group receiving intercultural sensitivity training with no training (t = -2.12, p = 0.042, p â¤ 0,05). Mean difference between the two groups showed that the treated group had a rate lower intergroup bias (mean = -6.44).